Indicators of biodiversity and carbon storage in remnant and planted vegetation in the Mount Lofty Ranges of South Australia: lessons for 'biodiverse' plantings. (24th May 2013) - Collard, Stuart; Fisher, Andrew; Hobbs, Trevor; Neumann, Craig
Summary Planting of woody perennial vegetation for carbon sequestration continues to gain momentum as markets for carbon develop in Australia. With the impetus of the Clean Energy Future package, these plantings have the potential to contribute to biodiversity gains if established and managed appropriately. In this study, we sought to link indicators of biodiversity to carbon storage in remnant vegetation, mixed‐species native revegetation and single‐species eucalypt plantations in the Mount Lofty Ranges (MLR) of South Australia. Native plant species richness was higher in remnant vegetation than in revegetation and plantation sites in the southern MLR, but only remnant and plantation sites were different in the northern MLR. Native bird species richness was higher in remnant than plantation sites, but revegetation sites were similar to both plantation and remnant sites in northern and southern sites. Mean total standing carbon varied across treatments in southern sites, and there were no statistically significant differences in mean carbon sequestration rate between planted treatments. Monoculture plantation sites lack the structural complexity required and offer limited resources for native fauna compared with mixed‐species revegetation or remnant vegetation. This reinforces the importance of carefully constructed incentives to compensate landholders for potential carbon shortfalls if the opportunity for biodiversity gains from carbon plantings is to be realised in the longer term. The value of the standing carbon in remnant vegetation should also be recognised in emerging markets.